Deep learning with R: by A. Ghatak, Singapore, Springer, 2019, 245 pp., €89.99, ISBN 978-981-13-5849-4. - Feng, Haoda; Liu, Hongqian (Innovation: The European Journal of Social Sciences, 2025)
The article focuses on "Deep Learning with R," a monograph by Abhijit Ghatak that explores the application of deep learning techniques using the R programming language, particularly in the context of natural language processing (NLP). The book provides a comprehensive guide, starting from fundamental concepts of machine learning and neural networks to practical applications in NLP, making it suitable for a wide audience, including novice researchers and experienced engineers. It covers various types of neural networks, optimization algorithms, and practical coding examples, emphasizing the advantages of using R for NLP tasks. The text highlights the book's structured approach and accessibility, making it a valuable resource for those interested in deep learning and AI engineering.